2016
DOI: 10.1055/s-0035-1565137
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Instrumented Insoles for Measuring Height in Vertical Jump

Abstract: The purpose of this study was to validate a new instrumented insole called ECnsole for measuring flight time during vertical jump performance. 66 participants performed 3 different jump tests (squat jump, countermovement jump and Abalakov jump) twice with flight times determined using an instrumented insole composed of 4 pressure sensors (PreECnsole) and an accelerometer sensor (AccECnsole), a laser platform (Sport Jump System Pro), and a high-speed motion capture system (HSC); the latter 2 systems are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…During the current study, a version of an instrumented insoles previously developed by the research group was used, called ECnsole, shown in Figure 1 [12,18]. The instrumented insoles contained four pressure sensors Flexiforce A401 (Tekscan, South Boston, MA, USA) located at the big toe, first and fifth metatarsal heads, and the heel.…”
Section: Materials and Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…During the current study, a version of an instrumented insoles previously developed by the research group was used, called ECnsole, shown in Figure 1 [12,18]. The instrumented insoles contained four pressure sensors Flexiforce A401 (Tekscan, South Boston, MA, USA) located at the big toe, first and fifth metatarsal heads, and the heel.…”
Section: Materials and Testingmentioning
confidence: 99%
“…Fatigue can be evaluated by quantifying maximal voluntary force, maximal voluntary shortening velocity, or power [11]. The height of a vertical jump, especially in the countermovement jump (CMJ), is commonly used to evaluate the legs muscular power [12] and to detect neuromuscular fatigue [13]. In addition, vertical jump has been used in several studies investigating the recovery time after fatigue interventions; however, further research is needed to elucidate the most relevant variables to analyze fatigue when the vertical jumps are employed [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A low-cost instrumented insole system designed by our research group was used ( Figure 1) for the dynamic pressure measurements. Our system was previously validated as a pressure-measuring instrument [39] using a commercial system, F-Scan (Tekscan, South Boston, MA, USA) and as a time-measuring system of physical activity in comparison with two gold standards [40]. With the aim of simplicity, each insole comprised a flexible polymeric film supporting a total of four piezoresistive pressure sensors located at the heads of the first and fifth metatarsals, at the first toe, and at the heel.…”
Section: Instrumented Insolesmentioning
confidence: 99%
“…In addition, the information collected from the sensors was processed in a datalogger fastened at the waist. More technical details of the instrumented insole system can be read elsewhere [39,40].…”
Section: Instrumented Insolesmentioning
confidence: 99%